"Run, Hide, Tell" or "Run, Hide, Fight"? The impact of diverse public guidance about marauding terrorist firearms attacks on behavioral intentions during a scenario-based experiment in the United Kingdom and Denmark. (15th June 2021) - Lindekilde, Lasse; Pearce, Julia; Parker, David; Rogers, Brooke
Abstract: Effective risk communication is an integral part of responding to terrorism, but public guidance about marauding terrorist firearms attacks is inconsistent. Following terrorist attacks involving mass shootings in Paris, France in November 2015, the UK police released a 'Stay Safe' film and leaflet that advises the public to 'Run, Hide, Tell' in the event of a firearms or weapons attack. However, in 2018 the Norwegian security authorities released different guidance, advising the public to 'Run', 'Hide', and if no other choice 'Fight'. While it is possible that following guidance to 'fight' may have saved lives during the 2019 Bærum mosque attack, this advice may also encourage risky behaviours. Conversely, current UK guidance has been shown to encourage protective behaviours but may also discourage people from taking action that could minimize the overall number of casualties. The purpose of the research presented here was to assess the degree to which the different guidance encourages protective behavioral reactions and discourages potentially dangerous actions. This was investigated using a cross-country comparative survey experiment (n = 5285) that employed two scenarios (based on proximity of attacker). The results show that both sets of guidance increase the likelihood of protective behaviors compared to a no guidance condition. However, while there is no evidence of the 'Run, Hide, Fight' guidance leading to unwarranted 'heroism', we find evidence that the 'Run, Hide, Tell' message may lead to increased likelihood of passivity in situations where more pro-active reactions would be beneficial.